Identifying challenges and potential solutions for sustainable kidney nutrition care delivery in selected Asian countries - Karupaiah, Tilakavati (Elsevier, 2023)
Background: Recent surveys highlight gross workforce shortage of dietitians in global kidney health and significant gaps in renal nutrition care, with disparities greater in low/low-middle income countries. Objective: This paper narrates ground experiences gained through the Palm Tocotrienols in Chronic Hemodialysis (PaTCH) project on kidney nutrition care scenarios and some Asian low-to-middle-income countries namely Bangladesh, India, and Malaysia. Method: Core PaTCH investigators from 3 universities (USA and Malaysia) were supported by their postgraduate students (n 5 17) with capacity skills in kidney nutrition care methodology and processes. This core team, in turn, built capacity for partnering hospitals as countries differed in their ability to deliver dietitian-related activities for dialysis patients. Results: We performed a structural component analyses of PaTCH affiliated and nonaffiliated (Myanmar and Indonesia) countries to identify challenges to kidney nutrition care. Deficits in patient-centered care, empowerment processes and moderating factors to nutrition care optimization characterized country comparisons. Underscoring these factors were some countries lacked trained dietitians whilst for others generalist dietitians or nonclinical nutritionists were providing patient care. Resolution of some challenges in low-tomiddle-income countries through coalition networking to facilitate interprofessional collaboration and task sharing is described. Conclusions: We perceive interprofessional collaboration is the way forward to fill gaps in essential dietitian services and regionalbased institutional coalitions will facilitate culture-sensitive capacity in building skills. For the long-term an advanced renal nutrition course such as the Global Renal Internet Course for Dietitians is vital to facilitate sustainable kidney nutrition care.